Translation grants in the exportation of Basque literature (2003-2021) - Manterola Agirrezabalaga, Elizabete (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2024)
This paper aims to delve into the circulation of translations from literature written in a small or lesser translated language into various foreign languages by examining subsidies given by source public institutions. Through a case study focused on Basque literature, this paper examines cultural policies as a tool for promoting a national cultural identity abroad and for enriching and gaining economic, social and cultural capital. By observing public subsidies awarded in the period 2003-2021 for the translation of literary works written by Basque authors, this paper offers a deeper knowledge of the exportation strategies of Basque literature. Therefore, the first stage of the analysis focuses on the characteristics of annual grants offered by Basque public institutions and the second stage examines the subsidised translations. One of the most significant results is that regional bodies stand out as those principally responsible for financially supporting the exportation of minority-language literature production. Moreover, the study demonstrates that books written in Basque are the main beneficiaries of the aid, compared to books written in Spanish. Another relevant conclusion is that intrastate translations, especially translations into Spanish, are significantly frequent compared to other target languages.